Adolescent / youth friendly community initiative (The Ministry GeorgetownGY, 2010)
Presents information on the adolescent / youth friendly community initiative, which seeks to establish spaces where young people can interact and develop key life skills, a joint project between the Ministry of Culture, Youth and Sport and UNFPA in Guyana.
Keywords: ADOLESCENTS